Line 1: 2x comes from taking the derivative of x^2+3 which the chain rule requires.
From line 2 you have
From the laws of exponents and surds we know that
Thus
When multiplying by 2x the 1/2 will cancel leaving you with
Which is line 3
if you have
y=SQUAREROOT (x^2 + 3)
let z = (x^2 + 3)
...1 dy/dz= 1/2 z ^-1/2 and dz/dx= 2 x <<< can someone explain where the 2 is derived from?
...2 then dy/dz x dz/dx = 1/2 z ^-1/2 (2 x)
...3 this = x/squareroot z = x/SQUAREROOT (x^2 + 3)
how do you get from line 2 to line 3 as x/SQUAREROOT (x^2 + 3)